THE RELATIONSHIP AMONG READING INTEREST, GRAMMAR KNOWLEDGE, AND READING COMPREHENSION OF NARRATIVE TEXT - Mujani, Sahril; Sofyan, Ahmad; Fahriany, Fahriany (Universitas Putera Batam, 2022)
Reading is a gate for grasping any insight of knowledge and science. The objective of the research was accepted to report the relationship among reading interest, grammar knowledge, and reading comprehension of narrative text. It was conducted to the tenth-grade students of State Islamic senior high school in State Islamic Senior High School 3 Pandeglang. The methodology applied was a quantitative and used a simple random sampling technique. Three instruments were used to obtain the data such as a questionnaire, grammar test and narrative test. The results of the study found that (1) there was a positive relationship between reading interest and reading comprehension in narrative text with the correlation value of 0.933, (2) there was a positive relationship between grammar knowledge and reading comprehension in narrative text with the correlation value 0.433, (3) there was a simultaneous relationship between reading interest and grammar knowledge to reading comprehension in narrative text with the correlation value 0.884. Therefore, it can be concluded that reading comprehension in the narrative text is contributed by students’ reading interest and grammar knowledge.